The impact of resistive electric fields on particle acceleration in reconnection layers. Issue 1 (3rd October 2022) - Puzzoni, E; Mignone, A; Bodo, G
ABSTRACT: In the context of particle acceleration in high-energy astrophysical environments featuring magnetic reconnection, the importance of the resistive term of the electric field compared to the convective one is still under debate. In this work, we present a quantitative analysis through 2D magnetohydrodynamic numerical simulations of tearing-unstable current sheets coupled to a test-particles approach, performed with the pluto code. We find that the resistive field plays a significant role in the early-stage energization of high-energy particles. Indeed, these particles are first accelerated due to the resistive electric field when they cross an X-point, created during the fragmentation of the current sheet. If this preliminary particle acceleration mechanism dominated by the resistive field is neglected, particles cannot reach the same high energies. Our results support therefore the conclusion that the resistive field is not only non-negligible but it does actually play an important role in the particle acceleration mechanism.